(3GdeYjGQ GdeYQH hGdLGeY GdeZQH Yf aJGhi YdeGA EaQjbjI hGdCfOdS hGdeZQHs - (3CHh GdYHGS CMeO Hf jMji Hf eMeO Hf YHO GdhGMO Hf Ydj GdhfTQjSj,J (B914 (3g` s
(3ChdgG (B:s
(3fhGRd GdfcGM SFd TjN TjhNfG CHh YHO Gddg eMeO Hf CMeO Hf eMeO Hf eQRhb Yf GdMceI ai MK QShd Gddg Ydi fcGM GdCHcGQ s
(3BNQgG (B:s
(3ajLH GdUOGb cGedkG HYO GdONhd dCfc YdeJ Cf GdQLhY HGdUOGb dXghQ GdeGfY ef OhGe GdfcGM hgPG THjg HbjGS GdeSGhGg GdefWbi hGdgfOSi Je GdSaQ GdKGfi s
(3HgG GdfcGM hGdNdY hGdfabg hGdMVGfI hGdQLYI hGdEHdGA hGdWgGQI hZjQgG ef CehQ GdfcGMs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3Ydi WQJgG Jedc HGSe EHQGgje Hh NQjSI s
(3cJHJ GdahGJM HGdCMeQ hGdCShO GdSejcjf s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdESdGejs